(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
Cultural heritage refers to historical objects that must be preserved through protection, development, and utilisation. In North Aceh Regency, cultural heritage preservation faces challenges such as low interest among younger generations and the lack of interactive learning media. This study aims to design a virtual tour application using Augmented Reality (AR) and Geographic Information System (GIS) technologies as an interactive medium to digitally introduce cultural heritage sites. Data were collected from the Department of Education and Culture of North Aceh and through direct observation and documentation in the field. The application integrates AR features to display 3D cultural objects and GIS to present the geographical locations accurately. The development includes user interface design, motion-based navigation, and historical information panels. Testing results show that all markers successfully displayed 3D objects with an average detection time of 3.58 seconds, a detection distance of 75.71 cm, and a rotation angle of up to 360°. The objects appeared stable, and the historical information was well presented. The main contribution of this study is the implementation of AR technology in the local context of North Aceh, which has rarely been applied. Limitations include the small number of heritage sites and testing limited to a few AR devices. Future research is recommended to expand site coverage, improve device compatibility, and add gamification features to enhance user engagement.